Experimental and numerical investigation of small punch creep test - Cortellino, Francesco (2015)
The small punch creep testing (SPCT) technique has received much attention because it can provide information on the creep behaviour of materials with a very small specimen being tested. However, the nature of the test is complex and several aspects of the behaviour of the specimen, characterised by various non-linear concurrent processes, still need investigation.